Estudio de la variabilidad genética de repoblaciones de QUERCUS ILEX L. SUBSP. BALLOTA (DESF.) SAMP. IN BOL. EN ANDALUCÍA - Burgarella, C.; NAVASCUÉS, M.; FICI, S.; LORA GONZÁLEZ, A. (IV Congreso Forestal Español, 2005)
An adequate management of the reproductive material for reforestation activities is fundamental in the conservation of forest genetic resources. In the present work the levels of genetic diversity and differentiation between artificial stands of Quercus ilex and the adjacent natural stands are assessed with nuclear microsatellites. Also, it was possible to analyse the natural population used as seed source for one of the reforestations studied. The levels of genetic differentiation between natural and artificial stands and the decrease of genetic diversity from the seed origin population to the reforestation are discussed in relation to the transference of seed among provenance regions and to the seed collection strategy (number of trees used for sampling seeds)
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: forest genetic resources; genetic contamination; microsatelites; seed collection